Displacement of maxillary dental implants: a case series on various scenarios - Anne-Kathrin Bär; Richard Werkmeister; Philipp Becker; Kim Lindwedel; Bilal Al-Nawas (BMC, 2024)
Abstract Background Oral rehabilitation with dental implants is a common procedure in modern dentistry due to its high success rates. However, complications such as implant displacement can occur, particularly in the maxillary region due to factors like atrophied maxilla, thin alveolar bone, and low bone density. This case series explores scenarios of maxillary dental implant displacement, emphasizing the impact of immediate preoperative imaging on patient outcomes. Case presentation Three cases of maxillary implant displacement are presented, each illustrating a different scenario. Complications resulting from the displacement of implants into adjacent structures such as the maxillary sinus and nasal cavity are described. All cases involved implants that were displaced during second-stage surgery, occurring four to six months post-implantation. Removal attempts used transnasal endoscopic, intraoral, or combined approaches, with only one implant successfully retrieved. Delays in surgery ranged up to 72 h, leading to one implant being swallowed and another unlocated. Outcomes varied, with some patients requiring hospitalization for up to five days. Conclusion This series highlights the crucial role of immediate preoperative 3D imaging in precisely locating displaced implants to ensure their safe and efficient removal. While implant displacement may not always be preventable, optimizing the timeframe between diagnostic imaging and surgical intervention can significantly enhance management. Accurately locating the implant minimizes treatment invasiveness and patient discomfort, thereby improving clinical outcomes.